Pricing New Corporate Bond Issues: An Analysis of Issue Cost and Seasoning Effects - FUNG, W. K. H.; RUDD, ANDREW (Journal of Finance, 1986)
ABSTRACT The pricing of new corporate bond issues is examined, with particular emphasis on the seasoning effect and the cost of underwriting. Considerable attention is paid to some special features of the corporate bond market, including the use of actual trader quotes so as to accurately measure holding period returns. Our results suggest that the cost of issuing corporate bonds is less than previously reported.